Edward Otis Hinkley, Supplement to the Maryland Code: Containing the Acts of the General Assembly Passed at the Session of 1864 Page 76 Image 153 (Vol. 2, 1865) § 12 - (:unkn) unknown (General Publisher, 1864)
Roads. § 12. No person shall fire any gun, pistol or firelock of any kind, on or within twenty yards of any public road, street, bridge, causeway or highway in Cecil county, under a penalty of not less than five nor more than twenty dollars, to be recovered in the same manner as prescribed in section one hundred and seventy seven of this Article.
--
Keywords: DISCHARGE